Proposta de um modelo para análise da gestão do desempenho em redes horizontais de empresas - Bonatto, Franciele (2015)
This study aims to propose a model for performance management analysis in horizontal networks of companies. For this, we carried out a systematic review, building a portfolio of articles based on the study of factors that affect performance in horizontal networks of companies and propose models and tools for analysis of performance management in these collaborative environments. From this portfolio defined the perspectives of evaluation and performance factors for the construction of the model. To structure the model we used the multi-criteria method to support decision AHP (Analytic Hierarchy Process) for the valuation and classification of levels of importance of perspectives assessment (PSPs). The values obtained by applying the AHP, together with the diagnostic performance factors of the structure, composed a diagram administration of the individual X-performance network performance management, which makes it possible to analyze the evolution of performance management on levels of network and individual level of each constituent company of this. Finally, the model was applied in a horizontal network of companies in the information technology sector in the city of Ponta Grossa, Paraná. The main results of this research, the model was consistent to generate diagnoses of the situation of companies, both individually and networking. It was also possible, using the developed model, make a specific diagnosis for each evaluation perspective, which makes it possible to perform a benchmarking between companies, providing a detailed and timely assessment of factors that compromise the company's performance at the individual level and global.